Lanthanide-doped inorganic materials and organic-inorganic hybrids for solid-state lighting - Ming Fang (2021)
The International Energy Agency estimated that lighting accounts for ~19% of the total worldwide energy consumption. Light emitting diodes (LEDs) have higher efficiency compared to that of conventional lighting sources. The commercial white-LEDs (WLEDs) are based on broad-band Y3Al5O12:Ce3+ (YAG:Ce) yellow phosphor in combination with blue LED chips through a low cost and simple procedure, in which the YAG:Ce phosphor is directly packed on the blue InGaN chip. However, such two colour-based WLEDs exhibit poor colour rendering index (CRI, usually <75), high correlated colour temperature (CCT, >6500 K), and chromaticity drifts, which cannot fully satisfy the applications of lighting and backlighting of the displays. Also, LEDs still face some other drawbacks such as the relatively low efficient green emission, termed the ³green gap´ issXe. A promising alternative strategy is based on the downshift of the electroluminescence of near ultra-violet (NUV)/blue LEDs into the green spectral region by UV/blue-down shifting phosphors. Thus, novel efficient white and green-emitting materials for the phosphor-converted LED applications are required. In this thesis, organic-inorganic hybrids (ureasils, d-U(600)) doped with green emitting Tb3+-based complexes were applied in combination with NUV-LED chips to fabricate efficient green LED prototypes. To improve CRI and CCT of commercial WLEDs, novel blue-light excited La2Ce2O7:Eu3+ red phosphors were also successfully synthesised and characterized. Moreover, tuned white light emitters involving d-U(600) hybrids doped with lanthanide (Ln3+=Tb3+, Eu3+)-based complexes, fluorescent dyes (e.g. coumarin), and carbon dots were also prepared and optically characterised revealing intriguing CCT, CRI and photostability towards novel WLEDs.